Review article: nucleos(t)ide analogues in patients with chronic hepatitis B virus infection and chronic kidney disease. Issue 1 (29th October 2013) - Pipili, C.; Cholongitas, E.; Papatheodoridis, G.
Summary Background The treatment of chronic hepatitis B (CHB) in patients with chronic kidney disease (CKD) is based on nucleoside (lamivudine, telbivudine, entecavir) or nucleotide (adefovir, tenofovir) analogues (NAs), but it may be complex and the information is scarce. Entecavir and tenofovir represent the currently recommended first‐line NAs for NA‐naive CHB patients, while tenofovir is the NA of choice for CHB patients with resistance to nucleosides. Aim To review the efficacy and safety of NAs in adult CHB patients with CKD and to provide reasonable recommendations for their optimal management. Methods Literature search in PubMed/Medline and manual search of relevant articles, reviews and book chapters. Results NAs are cleared by kidneys and their dosage should be adjusted in patients with creatinine clearance <50 mL/min. There are concerns about nephrotoxic potential of the nucleotides, particularly adefovir, while improvements of creatinine clearance have been reported under telbivudine. Most existing data in CHB patients with CKD are for lamivudine and, less frequently, for other NAs, mostly entecavir. Besides CHB, NA should be used in case of immunosuppressive therapy in any HBsAg‐positive patient with CKD including renal transplant (RT) recipients and in anti‐HBs‐positive recipients of kidney grafts from HBsAg‐positive donors. Conclusions Chronic hepatitis B patients with chronic kidney disease receiving nucleoside analogues should be followed carefully for treatment efficacy and renal safety. Despite the absence of strong data, entecavir and telbivudine seem to be the preferred options for nucleoside analogue‐naive CHB patients with chronic kidney disease, depending on viraemia and severity of renal dysfunction. More studies are certainly needed in this setting.